Long-term effects of the collagenase of the bacterium Clostridium histolyticum for the treatment of capsular fibrosis after silicone implants - Fischer, Sebastian; Diehm, Yannick; Henzler, Thomas; Berger, Martin R.; Hirche, Christoph; Kneser, Ulrich (Aesthetic plastic surgery, 2017)
BackgroundCapsular contracture remains the most frequent long-term complication after augmentation mammoplasty with silicone implants. Thereby, the main part of the fibrotic capsule is collagen. The collagenase of the bacterium Clostridium histolyticum is approved for the treatment of fibrotic diseases and has been demonstrated to be effective for capsular fibrosis treatment in the short term. However, long-term effectiveness is currently unknown but mandatory for clinical utilization.Materials and MethodsForty-eight rats received miniature silicone implants and an injection with either collagenase (treatment group) or plain solvent solution (control group) 120 days post insertion. Ten and 60 days after the injections, the rats underwent 7-Tesla magnetic resonance imaging (MRI) and high-resolution ultrasound (HR-US). Capsule tissue was harvested, and capsule thickness and collagen density were evaluated through histology. Furthermore, the expression levels of inflammatory (CD68, IL4, IL10, IL12, IL13), pro-, and anti-fibrotic (TGFb1, TGFb3, Smad3, Col1-4) genes were analyzed using qRT-PCR.ResultsOn days 10 and 60 after injection of collagenase, histology showed that capsule thickness was significantly reduced in the treatment group when compared with the control (p < 0.05). Thickness measurements were verified by MRI and HR-US analysis. Skin perforation occurred in two cases after collagenase injection. The initial up-regulation of pro-fibrotic and inflammatory genes 10 days after collagenase injection did not persist in the long term. Contrarily, on day 60, a slight trend towards lower expression levels with a significant down-regulation of TGFb3 was detected in the treatment group.ConclusionThe collagenase of the bacterium C. histolyticum effectively degrades capsular fibrosis around silicone implants with stable outcomes throughout 60 days post injection. Skin perforation and adequate and uniform drug distribution within the implant pocket are issues that need to be addressed. Further studies are warranted to clarify whether collagenase injections have the potential to become a viable treatment option for capsular contracture.No Level AssignedThis journal requires that authors 46 assign a level of evidence to each article. For a full 47 description of these Evidence-Based Medicine ratings, 48 please refer to the Table of Contents or the online 49 Instructions to Authors. www.springer.com/00266.
Published online: 23 December 2016
Gesehen am 21.08.2019